The 2018 Lake Louise Acute Mountain Sickness Score - Roach, Robert C.; Bärtsch, Peter (High altitude medicine & biology, 2018)
Abstract Roach, Robert C., Peter H. Hackett, Oswald Oelz, Peter Bärtsch, Andrew M. Luks, Martin J. MacInnis, J. Kenneth Baillie, and The Lake Louise AMS Score Consensus Committee. The 2018 Lake Lou...